The Role of Teachers in Integrating Audio Visual Media to Improve Students' Understanding of History Subjects in Class XI of SMA Negeri 1 Sarjo - Irma; Hasan; Iskandar; Kapile, Charles (Kirana Publisher (KNPub), 2025)
The purpose of this study is to analyze the role of teachers in integrating audio-visual media in class XI of SMA Negeri 1 Sarjo and the effect of using audio-visual media on improving students' understanding of history in class XI of SMA Negeri 1 Sarjo. This study is useful for enriching the theory of learning history through audio-visual media, as well as helping teachers, students, and schools in improving the effectiveness, understanding, and quality of learning. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study show 1) that teachers play a role as active facilitators in designing and implementing audio-visual media such as PowerPoint (PPT) and videos in the learning process. The integration of these media creates a more interesting, fun, and interactive learning atmosphere. The use of audio-visual media has been proven to have a positive influence on students' understanding. 2) The effect of using audio-visual media on improving students' understanding of history in class XI of SMA Negeri 1 Sarjo, this is evidenced by students' responses that show higher enthusiasm and concentration during the learning process. The majority of students stated that they found it easier to understand the material when teachers used audio-visual media compared to conventional lecture methods and showed increased daily test scores. Therefore, the use of audio-visual media in history learning is highly recommended to create meaningful and adaptive learning to the needs of the digital generation.